Analisis Faktor–Faktor yang Mempengaruhi Permintaan Kredit Gadai di Pegadaian Cabang Ende - Lerang, Agustinus Owentus; Leha, Ernesta; Penu, Yustina Paulina (JURNAL EQUILIBRIUM, 2023)
The abstract is a brief summary of the entire article’s contents. The abstract is written clearly, concisely and using powerful sentences in a paragraph of 150-200 words. The abstract should be able to help the reader understand the points out the essential parts of the article. It should give a clear general description of the article’s contents. Abstract writing consists of four main parts arranged in sequence. The first part explains the primary objectives and research problem(s)discussed. The second part explains basic design of research methods. The third part explains the major findings or results as the results of the analysis. The fourth part outlines the interpretation and conclusions. Abstracts are not allowed to put an extensive background, cite a literature, using abbreviations or unfamiliar terms, include sort statistics, tables, figures or references to those tables/figures. The abstract is not allowed to add information not contained in the original work. The abstract is not for defining a term. The abstract is presented in both Bahasa Indonesia and English.